Technological parameters of sheep wool in imported breeds obtained by embryo transfer, raised under the conditions of the central highlands of Peru - Pantoja Aliaga, César (2022)
The aim of this study was to determine the technological parameters of the fibre of wool and meat sheep breeds obtained by transfer of embryos imported from Australia and intended for the improvement of sheep herds in the central highlands of Peru. The study was carried out at the Casaracra Experimental Center of the Daniel Alcides Carrión National University, Junín Region, Peru, at 3772 meters above sea level. The breeds were East Friesian, Poll Dorset, Corriedale, Texel, Merino Dohne, and Finnish Landrace. The linear additive model included the factors breed, sex, age and corporal region of sampling, while the interactions were considered residual. An inverse association was found between fibre diameter and crimp curvature (-0.59) and with comfort factor (-0.98); likewise between the crimp curvature with the staple length (-0.43); On the other hand, the association was direct between the comfort factor and crimp curvature (0.55). Females (28.5±0.42 µm), milk teeth (26.4±0.95 µm) and Merino Dohne (18.5±0.45 µm) showed a smaller fibre diameter compared to males, other age groups and breeds, respectively. The Merino Dohne can be implemented in improved medium-fine herds (Finnish Landrace, Corriedale), while the East Friesian, Texel, Poll Dorset and the cross of Texel with Poll Dorset could be introduced in Creole herds.